2014
DOI: 10.1007/s10562-014-1394-2
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Surface CrOx Sites on SiO2 in Different Environments

Abstract: This perspective article critically reviews the catalysis literature on the nature of the surface CrO x sites present on SiO 2 in different environments. The recent application of in situ spectroscopic techniques that directly monitor the surface chromia sites on silica in different environments has significantly improved our fundamental understanding of supported CrO x /SiO 2 catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
1
31
0
2
Order By: Relevance
“…The spectroscopic properties of Cr 6+ on Al 2 O 3 are well known in the specialized literature. While for Cr 6+ on SiO 2 there is still a debate on the aggregation state of the Cr 6+ species (both mono-and dichromates have been proposed [5, 7-9, 20, 22-24, 26, 34, 35], or even mono-oxo CrO 5 [27][28][29][30][31][32][33]), Cr 6+ exist primarily as monochromate species on Al 2 O 3 [9,[19][20][21][22][23][24]36] (the corresponding DR UV-Vis-NIR spectrum is shown in Figure S1a). Temperature-programmed reduction measurements have demonstrated that Cr 6+ on Al 2 O 3 are more reducible than Cr 6+ on SiO 2 (i.e.…”
Section: The Role Of Co and H 2 As Reducing Agents For Cr 6+ /Al 2 Omentioning
confidence: 99%
“…The spectroscopic properties of Cr 6+ on Al 2 O 3 are well known in the specialized literature. While for Cr 6+ on SiO 2 there is still a debate on the aggregation state of the Cr 6+ species (both mono-and dichromates have been proposed [5, 7-9, 20, 22-24, 26, 34, 35], or even mono-oxo CrO 5 [27][28][29][30][31][32][33]), Cr 6+ exist primarily as monochromate species on Al 2 O 3 [9,[19][20][21][22][23][24]36] (the corresponding DR UV-Vis-NIR spectrum is shown in Figure S1a). Temperature-programmed reduction measurements have demonstrated that Cr 6+ on Al 2 O 3 are more reducible than Cr 6+ on SiO 2 (i.e.…”
Section: The Role Of Co and H 2 As Reducing Agents For Cr 6+ /Al 2 Omentioning
confidence: 99%
“…[9,246] Theinitial CrO 3 / SiO 2 contains predominantly Cr VI -dioxo surface complexes (SiO) 2 Cr(=O) 2 (Scheme 16), [247][248][249][250] although small amounts of EPR-active Cr sites are also present. [9,246] Theinitial CrO 3 / SiO 2 contains predominantly Cr VI -dioxo surface complexes (SiO) 2 Cr(=O) 2 (Scheme 16), [247][248][249][250] although small amounts of EPR-active Cr sites are also present.…”
Section: Phillips and Union Carbide Catalystsmentioning
confidence: 99%
“…[9,246] Theinitial CrO 3 / SiO 2 contains predominantly Cr VI -dioxo surface complexes (SiO) 2 Cr(=O) 2 (Scheme 16), [247][248][249][250] although small amounts of EPR-active Cr sites are also present. [250,256,257] Themetal sites can be reduced by reaction with CO. [258][259][260][261][262][263] Ther educed Cr sites react with ethylene immediately,w hich suggests that the active site is present after reduction by CO.D etailed studies showed that this reduced material contains mostly Cr II sites. [250,256,257] Themetal sites can be reduced by reaction with CO. [258][259][260][261][262][263] Ther educed Cr sites react with ethylene immediately,w hich suggests that the active site is present after reduction by CO.D etailed studies showed that this reduced material contains mostly Cr II sites.…”
Section: Phillips and Union Carbide Catalystsmentioning
confidence: 99%
“…Die aktiven Zentren des Phillips‐Katalysators waren bereits Thema zahlreicher Untersuchungen . Das Ausgangsmaterial, CrO 3 /SiO 2 , enthält vorwiegend Cr VI ‐Dioxo‐Oberflächenkomplexe (≡SiO) 2 Cr(=O) 2 (Schema ), aber auch geringe Mengen an EPR‐aktiven Cr‐Zentren . In Gegenwart von Ethylen werden die Cr VI ‐Dioxo‐Zentren zu Cr II ‐Zentren als wichtigste Oberflächenspezies und zu einer kleinen Menge Cr III ‐Zentren reduziert.…”
Section: Alkenpolymerisationunclassified
“…Das Ausgangsmaterial, CrO 3 /SiO 2 , enthält vorwiegend Cr VI ‐Dioxo‐Oberflächenkomplexe (≡SiO) 2 Cr(=O) 2 (Schema ), aber auch geringe Mengen an EPR‐aktiven Cr‐Zentren . In Gegenwart von Ethylen werden die Cr VI ‐Dioxo‐Zentren zu Cr II ‐Zentren als wichtigste Oberflächenspezies und zu einer kleinen Menge Cr III ‐Zentren reduziert. Die Metallzentren können auch durch Reaktion mit CO reduziert werden .…”
Section: Alkenpolymerisationunclassified